Exploring Digital News Publishing Business Models: A production network approach - Kasper Lindskow (Copenhagen Business School (CBS), 2016)
News publishers in the industrialized world are experiencing a fundamental challenge to their business models because of the changing modes of consumption, competition, and production of their offerings that are associated with the emergence of the networked information society. The erosion of the traditional business models poses an existential threat to news publishing and has given rise to a continuing struggle among news publishers to design digital business models that will be sustainable in the future. This dissertation argues that a central and underresearched aspect of digital news publishing business models concerns the production networks that support the co-production of digital news offerings. To fill this knowledge gap, this dissertation explores the strategic design of the digital news publishing production networks that are associated with HTML-based news offerings on the open Web. In order to do so, a theoretical model is developed that is suited for the analysis of the strategic design of business models, including the production networks that support them, in the sectors of the economy that are affected by networked informatization in general and in digital news publishing specifically. The theoretical model includes a business model construct that enables a detailed analysis of production networks and an integrated strategy theory that combines networked-based approaches to value creation and capture with Emerson's power-dependence theory in order to conceptualize both collaboration and competition strategies. In addition, a novel method is developed that can be used to collect and analyze very large amounts of data on the resource exchanges that take place between news publishers and their business partners. The method allows for systematic mapping of the flows of resources in digital news publishing ecologies and of the production networks that are associated with the co-production of digital news offerings. The theoretical model and methodology developed in the dissertation are used to explore the American digital news publishing ecology and the strategies that 41 different leading American news publishers use to design their production networks. In the analysis, the activities carried out by and resource flows between a total of 1,356 business partners and news publishers in the American digital news publishing ecology are identified and visualized. In addition, a fundamental architecture that is shared by all digital news publishing production networks and a typology of 9 different types of production networks are identified. Furthermore, it is found that the structure of the American digital news publishing ecology is highly asymmetric and gives rise to a number of specific strategic dilemmas for news publishers. Finally, 9 different types of strategies that news publishers use to design their production networks, each of which mediates the dilemmas they face in different ways, are identified. In the conclusion to the dissertation, the findings of the dissertation are discussed, put into perspective, and connected to the existing research on other elements in digital news publishing business models in order to bring us closer to a holistic theory of the strategic design of digital news publishing business models.
hdl:10398/9284
Keywords: 650